Does one size fit all? The sector-specific impact of R&D investment intensity and CEO educational backgrounds on corporate social responsibility performance - Al-Dubai, Shehabaddin Abdullah Abdulwadod (Edelweiss Applied Science and Technology, 2025)
Researchers emphasize the importance of CEOs' educational backgrounds in shaping the internal mechanisms of corporate governance, with recent scholarly studies highlighting the profound influence of CEOs' attributes on CSR performance. This study aims to investigate the role played by CEOs who acquired university, postgraduate, and business education, along with R&D investment intensity, on the CSR performance of manufacturing and service companies. Utilizing data from 1,632 firm-year observations of companies listed in China between 2015 and 2020, the study reveals that service companies with low-intensity R&D investment and led by CEOs with postgraduate degrees appear to outperform others in terms of CSR. However, the conclusions vary when the two sectors are examined separately. Manufacturing companies with low-intensity R&D investment outperform their counterparts in the same sector only when their CEOs have postgraduate and business education. On the other hand, service-oriented firms exhibit enhanced performance under the leadership of CEOs lacking formal business education, particularly when coupled with low R&D investment intensity. This observation contradicts the widely held assumption that MBA-educated executives are inherently more effective in driving and sustaining CSR initiatives. This study acknowledges that one size does not fit all, as CEOs' educational backgrounds have different impacts on different companies.